Case study: Exploration and exploitation of hydrocarbons at the sea in Argentina – Is knowledge co-created or only a non-binding formal requirement? - Radovich, Violeta Soledad (2023)
The objective of this case study is to introduce environmental law in Argentina andfocus on the role of coproduction of knowledge regarding the new permits to explore and exploithydrocarbons at the sea granted in 2021. The methodology is based on analysis of laws, deeds ofpublic hearings, interdisciplinary scientific articles and judicial decisions.In Argentina, the right to a healthy environment is guaranteed by the Constitution. Moreover, asregards participatory processes in environmental matters, the Escazú Agreement (EA) also hasconstitutional status in the country.Results show that in Argentina, public hearings shall be carried out previous to authorizingactivities that may cause negative effects over the environment; however, the results of thesepublic hearings are not legally binding. This means that public hearings are a mere proceduralguarantee, a uni-directional administrative procedure governed by States that have the last wordon the final decision.Social movements and organizations, as well as scientists oppose to these permits and claim thatthis activity needs a “social license”, which was not granted during the public hearing becauseonly four percent of the participants voted in favor of granting the permits. One of the mostrepeated claim in the hearing was that results should be binding. People have established NGOs,such as Asamblea por un mar libre de petroleras, and express their concern in social media andby organizing rallies in the streets.Although only four per cent voted in favour of granting the permits, six months after the hearingthe permits were granted. However, a federal judge suspended this permit after an amparo actionwas filed by affected citizens.